The impact of parental overprotection on the emotions and behaviors of pediatric hematologic cancer patients: a multicenter cross-sectional study - Yu, Yahui; Zheng, Xiaofeng; Xu, Wenjing; Huang, Yuru; Wang, Xulu; Hong, Wanting; Wang, Runping; Ye, Xiaojing; Zhang, Chunmei (Frontiers in Psychology, 2024)
Background Parental overprotection may have an impact on children’s emotional and behavioral problems (EBPs). As pediatric hematologic cancer patients have compromised immune systems, parents of such children often worry excessively, interfering with their daily lives. Therefore, avoiding overprotection is crucial for the overall physical and mental health of pediatric hematologic cancer patients. Aims The aim of this study was to examine the current status of EBPs in pediatric hematologic cancer patients and analyze their associated risk factors. Design This work was a multicenter cross-sectional observational and correlational study. We collected data anonymously through parental questionnaires from three pediatric hematologic oncology hospitals in China. The Strengths and Difficulties Questionnaire, the Parental Overprotection Measure (POM) scale, and a general information survey designed by the research team were employed to assess children’s EBPs, the degree of parental overprotection, as well as basic demographic and disease-related information. Chi-square tests and generalized linear mixed-effects regression analysis were used to analyze the factors influencing EBPs among the pediatric hematologic cancer patients. Setting and participants Using a convenience sampling method, a total of 202 participants’ parents were selected. All participants were invited to complete the questionnaire through one-on-one guidance. Results Emotional symptoms accounted for the highest proportion of abnormal EBPs in children (27.72%), followed by peer problems (26.24%), prosocial behavior (25.74%), behavioral problems (14.36%), and total difficulties (13.86%). A minority of children had abnormal hyperactivity scores (4.95%). The results of a generalized linear mixed regression analysis showed that age, duration of illness, and parental overprotection were significant factors influencing abnormal EBPs in children (p < 0.05). A POM score threshold of 37 exhibited good sensitivity (74%) and specificity (90%) in predicting abnormal EBPs in children. Conclusion Pediatric hematologic cancer patients under excessive parental protection are more prone to experiencing EBPs. Healthcare professionals should guide parents to reduce this excessive protection, thus mitigating the occurrence of EBPs in children.